Effects of a Moderate or Aggressive Implant Strategy on the Rumen Microbiome and Metabolome in Steers - Henniger, Madison T.; Wells, Jim E.; Hales, Kristin E.; Lindholm-Perry, Amanda K.; Freetly, Harvey C.; Kuehn, Larry A.; Schneider, Liesel G.; McLean, Kyle J.; Campagna, Shawn R.; Christopher, Courtney J.; Myer, Phillip R. (Frontiers in Animal Science, 2022)
The effects of growth-promoting implants have been well-defined for their ability to impact growth performance in beef cattle. Production-relevant microbes and microbiomes in the rumen have also been associated with growth traits. However, the role of implants on the rumen microbiome has not been determined. The objective of this study was to determine if different doses of implant hormones cause gain-associated ruminal microbial community changes. To assess this, a completely randomized design was used and 336 fall-born steers 450 to 470 days of age from the germplasm evaluation population at the US Meat Animal Research Center (Clay Center, NE) were divided into two treatment groups: 1) a moderate implant strategy (n = 167) of Revalor-IS (80 mg trenbolone acetate and 16 mg estradiol) followed by Revalor-S (120 mg trenbolone acetate and 24 mg estradiol) or 2) an aggressive implant strategy (n = 169) of Revalor-IS followed by Revalor-200 (200 mg trenbolone acetate and 20 mg estradiol). Steers were fed the same diet (57.0% dry-rolled corn, 30% wet distiller’s grains with solubles, 8.0% alfalfa hay, 4.25% vitamin and mineral supplement, and 0.75% urea, on a DM basis). On d 85 after implants administration, rumen contents were collected via orogastric tubing. Samples were sequenced to target and identify bacteria, archaea, and protozoa. Untargeted metabolomics was performed on rumen content using ultra high performance liquid chromatography high resolution mass spectrometry. Production data between implant strategies was analyzed using a mixed model ANOVA (SASv9.4, Cary, NC) followed by separation of least squares means. Microbial diversity between strategies did not differ for archaea or protozoa (P > 0.05). Average daily gain was different (P = 0.01; 1.72 vs 1.66 ± 0.02 kg, aggressive vs moderate, respectively); however, large microbial community shifts were not associated with implant strategy. Two metabolites, N-acetyllysine and N-acetylornithine, were found in greater abundance in the moderate implant strategy (P ≤ 0.04). Understanding associations between the rumen microbiome and implant strategies may allow improvement of growth efficiency in beef cattle.